Synergistic Roles of Curcumin in Sensitising the Cisplatin Effect on a Cancer Stem Cell-Like Population Derived from Non-Small Cell Lung Cancer Cell Lines - Abdul Satar, Nazilah (Molecules, 2021)
Cancer stem cells (CSCs) represent a small subpopulation within a tumour. These cells possess stem cell-like properties but also initiate resistance to cytotoxic agents, which contributes to cancer relapse. Natural compounds such as curcumin that contain high amounts of polyphenols can have a chemosensitivity effect that sensitises CSCs to cytotoxic agents such as cisplatin. This study was designed to investigate the efficacy of curcumin as a chemo-sensitiser in CSCs subpopulation of non-small cell lung cancer (NSCLC) using the lung cancer adenocarcinoma human alveolar basal epithelial cells A549 and H2170. The ability of curcumin to sensitise lung CSCs to cisplatin was determined by evaluating stemness characteristics, including proliferation activity, colony formation, and spheroid formation of cells treated with curcumin alone, cisplatin alone, or the combination of both at 24, 48, and 72 h. The mRNA level of genes involved in stemness was analysed using quantitative real-time polymerase chain reaction. Liquid chromatography-mass spectrometry was used to evaluate the effect of curcumin on the CSC niche. A combined treatment of A549 subpopulations with curcumin reduced cellular proliferation activity at all time points. Curcumin significantly (p < 0.001) suppressed colonies formation by 50% and shrank the spheroids in CSC subpopulations, indicating inhibition of their self-renewal capability. This effect also was manifested by the down-regulation of SOX2, NANOG, and KLF4. Curcumin also regulated the niche of CSCs by inhibiting chemoresistance proteins, aldehyde dehydrogenase, metastasis, angiogenesis, and proliferation of cancer-related proteins. These results show the potential of using curcumin as a therapeutic approach for targeting CSC subpopulations in non-small cell lung cancer.